Furfural Removal from Refinery Wastewater by Adsorption on Commercial Activated Carbon - Ghazy, Rouaa N.; Shakir, Ibtehal K. (Journal of Petroleum Research and Studies, 2022)
Furfural is a toxic aromatic aldehyde that can cause severe environmental problems, especially the wastewater discharge from petroleum refinery units. The effect of adsorption variables, which include time (30-240) min, initial concentration of furfural (40-5080) mg/l, and amount of adsorbent material (10, 15, and 20 g\250 ml). The commercial activated carbon was investigated in a batch process in order to obtain the maximum furfural removal from wastewater. The results obtained from the experimental investigations showed that furfural removal increases with the increasing adsorbent material and decreases with increasing furfural concentration. Best Furfural removal efficiency was obtained at pH value equal 7.0, agitation speed 150 rpm, contact time 240 minutes. Chemical adsorption takes place when increasing temperature adsorption capacity increases. The best solvent used to regenerate activated carbon was ethanol 50 wt%. Ethanol has been used in industrial applications due to its low cost and relatively eco-friendly solvent. The laboratory experiments were done, and the sump drum O3D4, D-303 site was chosen to execute the project. The maximum contamination in the furfural was 100 ppm. The dimension of the polluted area in the sump drum (O3D4, D-303) was 20.3, 45 m2. The amount of activated carbon used 327, 726.3 kg.